THE ECONOMICS OF AGRICULTURAL SUSTAINABILITY ANALYZING COST-PRODUCTION DYNAMICS AND POLICY IMPLICATIONS FOR FUTURE FARMING MODELS - Layla Al-Khaled; Ahmed Al-Sabah; Putu Fajar Kartika Lestari (Yayasan Adra Karima Hubbi, 2026)
The transition toward agricultural sustainability has intensified debates on the economic viability of farming systems under rising input costs, environmental constraints, and policy reforms. Conventional production models often prioritize short term output gains, overlooking long-term cost efficiency, resource depletion, and externalities that undermine farm profitability and resilience. This study aims to analyze the cost production dynamics of sustainable agricultural practices and examine their policy implications for future farming models. The research employed a mixed methods economic analysis combining farm-level cost and production data, comparative efficiency assessment, and secondary policy review. Quantitative indicators included input costs, output value, productivity ratios, and profitability margins, while policy instruments were analyzed to assess incentive structures and regulatory impacts. The results indicate that sustainable farming systems demonstrate higher cost efficiency over time through reduced dependency on external inputs and improved resource-use productivity, despite moderate initial transition costs. Policy support mechanisms, such as subsidies, price incentives, and technical assistance, significantly influenced adoption outcomes and economic performance. The study concludes that sustainable agriculture can be economically competitive when supported by coherent policy frameworks that internalize environmental benefits and reduce transition risks. Integrating economic analysis with sustainability-oriented policies is essential for shaping resilient and economically viable future farming models.